Disrupted sleep predicts next day agitation following moderate to severe brain injury. (29th July 2019) - Draganich, Christina; Gerber, Don; Monden, Kimberley R.; Newman, Jody; Weintraub, Alan; Biggs, Jennifer; Philippus, Angela; Makley, Michael
ABSTRACT: Objective : Disrupted sleep is common during acute recovery from traumatic brain injury (TBI) and has been linked to daytime agitation. This study investigated the relationship among nighttime sleep efficiency (SE), total sleep time (TST), wakefulness after sleep onset (WASO), and number of wake bouts (NWB) as measured by actigraphy to observer ratings of agitation for patients with TBI who were undergoing inpatient rehabilitation. Methods : This is a retrospective, observational study of a convenience sample of 65 individuals admitted to TBI inpatient rehabilitation who were monitored with actigraphy and the Agitated Behaviour Scale (ABS) for the first 72 h. Each patient's average SE, TST, WASO, and NWB for the 72-h period was calculated using actigraphy for the rest interval from 2100 to 0700. Daily ABS scores were obtained for each day following the nighttime sleep period. Results : Patients were not significantly different on age, gender, etiology of injury, days post-injury, rehabilitation length of stay, or severity of injury as measured by length of posttraumatic amnesia (PTA). SE and TST were significantly lower for patients with agitation than for patients without agitation. Conclusions : This study suggests a relationship between disrupted sleep and agitation for patients with TBI who are undergoing inpatient rehabilitation.